Experimental analysis of reinforcing columns of reinforced concrete, with anchor steel bolts - A. C. MESQUITA; A. S. ROCHA; R. G. DELALIBERA; W. A. DA SILVA (Revista IBRACON de Estruturas e Materiais)
Abstract This article presents a columns reinforcement experimental study, with the use of anchor steel bolts and fill with self-compacting concrete. Were tested five columns of reinforced concrete subjected to flexion-compression: two columns were used as reference, and a cross-section equal to 120 x 250 mm; with a monolithic section equal to 155 x 250 mm cross section of the same reinforced columns and three which were initially molded with a 120 x 250 mm section and subsequently received a layer of 35 mm thick self-compacting concrete in the compressed side. Despite the studs do not present break, there was peeling of the reinforcement layer. The results indicate the possibility of using this method in reinforcing structural rehabilitation of reinforced concrete columns, with increase in load capacity on average equal to 403% in relation to the column reference.